Determinan Pengangguran Lulusan SMK Provinsi Sulawesi Utara Sebelum dan Saat Pandemi Covid-19 - Tengku Mashitah Crisanty; Ernawati Pasaribu (Seminar Nasional Official Statistics, 2022)
Indonesia is facing a demographic bonus phenomenon and the Covid-19 pandemic. As a result of the Covid-19 Pandemic, to reduce the spread of the Covid-19 virus, the government imposed PSBB which had an impact on reducing employees (PHK). One way to overcome unemployment is the implementation of vocational revitalization. However, the impact of the revitalization of SMK has not been seen as evidenced by the TPT of SMK graduates who are still the largest contributor to Indonesian unemployment in 2018 to 2021. North Sulawesi is one of the provinces that has a high TPT of SMK graduates. This study uses data from the August 2019 and 2021 National Labor Force Survey (Sakernas). The analytical method used is binary logistic regression. The results showed that in 2019 the independent variables that had a significant effect on unemployment status were marital status, field of expertise and year of graduation. Meanwhile, in 2021, the independent variables that have a significant effect on unemployment status are job training, marital status, year of graduation and area of ​​residence.